2016
DOI: 10.5130/ajceb.v16i3.5164
|View full text |Cite
|
Sign up to set email alerts
|

An innovation resistance factor model

Abstract: The process and implementation strategy of information technology in construction is generally considered through the limiting prism of theoretical contexts generated from innovation diffusion and acceptance. This research argues that more attention should be given to understanding the positive effects of resistance. The study develops a theoretical framing for the Integrated Resistance Factor Model (IRFM). The framing uses a combination of diffusion of innovation theory, technology acceptance model and social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Prior researchers’ use of technology adoption models for understanding ICT in the construction industry has been criticized for concentrating on information systems adoption, while few studies have had a focus on adoption of tools and equipment (Sepasgozar et al , 2016). In their integrated resistance factor model, Ishak and Newton (2016) combine elements of diffusion of innovation, UTAUT and social network threshold theory. Their empirical findings indicate four significant constructs explaining user resistance, including compatibility and complexity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior researchers’ use of technology adoption models for understanding ICT in the construction industry has been criticized for concentrating on information systems adoption, while few studies have had a focus on adoption of tools and equipment (Sepasgozar et al , 2016). In their integrated resistance factor model, Ishak and Newton (2016) combine elements of diffusion of innovation, UTAUT and social network threshold theory. Their empirical findings indicate four significant constructs explaining user resistance, including compatibility and complexity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study concluded that UTAUT provides the best predictive performance (Okpala et al 2021b). It is also important to note that very few studies complemented TAM with theories focused on inhibitors or resistance Wang et al 2020;Ishak and Newton 2016). While focusing on factors that encourage and enable the use of technology is worthwhile, investigating the inhibitors to technology acceptance through a theoretical lens is critical, especially in industries known to be resistant to innovation.…”
Section: Rq4: Models and Key Constructs For Assessing Technology Acce...mentioning
confidence: 99%
“…The presentation of resistance had the possibility to set the functional monarchies of a technology in the instant context of current work practices, it could be viewed as a fundamental mechanism to better sensed how users actually and are could respond to new technology innovations (Mohd Ishak and Newton, 2016). Resistance might accord when the innovation obstructs established routines, habits, traditions and norms or causes conflicts with consumers' views, values and faith of consumers.…”
Section: Innovation Resistance Theorymentioning
confidence: 99%